Maybe You Should Talk to Someone: The Role of Online Communities on Mental Healthcare Presenter Information - Ghosh, Soham (My University, 2023)
Online Health Communities like YouTube offer mental health patients an alternative channel to learn about mental illnesses, the treatment path to follow, and to share their experiences. For many patients who are reluctant to seek professional help, a video on mental health uploaded by a content creator may serve as a substitute for a counsellor. Our work aims to develop an understanding of the relationship between language formality and social support and provide normative guidelines for content creators on social media platforms. Using two transformer-based deep learning classification models, we determine the degree of language formality or informality present in the content, and three dimensions of social support in the comments. We then utilize propensity score estimation to establish the causal effect of (in)formality on the dimensions of social support for 994 videos and 3,10,157 comments. Our findings indicate that informal speech increases emotional support, leading to better health outcomes.
International Conference on Information Systems
PUBLISHED
India
Keywords: Online Health Communities (OHCs), mental health, deep learning, social media, healthcare analytics; Digital Humanities; Identification and quantification of health care needs